The devolution revolution: Implications for agricultural service delivery in Ghana - Resnick, Danielle (International Food Policy Research Institute, 2018)
In 2009, Ghana began pursuing the devolution of functions and responsibilities from the central government to the country’s 216 Metropolitan, Municipal, and District Assemblies (MMDAs). Agriculture was among one of the first sectors to be devolved, a process that became effective in 2012. This paper analyzes how this transition has proceeded, with a focus on the implications for agricultural civil servants within the MMDAs, accountability to citizens, and agricultural expenditures. Empirically, the paper draws on a survey of 960 rural households, 80 District Directors of Agriculture (DDAs), district level budget data from 2012 to 2016, and semi-structured interviews with a range of national and local government stakeholders.